Analysis of the quality of students science research ideas through the implementation of research-based learning models - Syazali, Muhammad; Widiada, I Ketut; Zain, Mohammad Irawan (Jurnal Pijar Mipa, 2023)
Learning that focuses on achieving product mastery is not optimal in facilitating students to create quality research ideas. In this research, we implemented MPBR to analyze the quality of science research ideas from students. To collect research ideas from students, the documentation method is used. Documents as qualitative instruments obtained through this method are assessed based on four criteria. They are suitability to the scope of scientific studies, the presence of research problems, the accuracy of the editorial title formulated from the research problem, and the urgency of the study variables. The data obtained was analyzed quantitatively and qualitatively. The quantitative analysis that we carry out is proportion analysis. The qualitative analysis includes data reduction, visualization, and conclusion. We found that all research ideas are within the scope of scientific studies and are based on research problems. However, only some scientific research ideas have appropriate title formulations, and the variables need to be studied further through the research process. This has implications for the overall quality of research ideas. The quality of research ideas in the outstanding category is 44.06%. The proportion in the good category is 14.68%, and the remainder is in the fair category, with a ratio of 41.26%. The conclusion is that implementing the PBR model effectively trains students to create scientific research ideas based on problems they find in the surrounding environment.